Effect of Flue Gas Composition on Mercury Removal by Injecting Rice Husk-Derived Activated Carbon - Jun TAO; Xiaobing GU; Tianfang HUANG; Shuai LIU; Peng HU; Lu DONG; Yaji HUANG; Yufeng DUAN (Zhongguo dianli)
The flue gas mercury removal experiment was carried out on a 0.3MW pilot scale circulating fluidized bed test facility by injecting biomass based activated carbon which is originally derived from rice husk and then modified by halogenated ammonium. Effects of exit temperature of the SCR and flue gas, concentration of SO2 and NO on the injection demercuration efficiency were discussed. The ASTM Standard D 6784-02 (OHM Ontario Method) was applied to measure the concentration of mercury from the coal-fired flue gas. The results showed that both the mercury removal efficiency and elemental mercury conversion efficiency go up with the elevated flue gas temperature; The existence of NO can enhance the mercury removal effect but SO2 will inhibit it on the other way. The mercury removal efficiency could reach about 90% with this modified type of activated carbon sprayed into flue gas under the conditions of SCR inlet temperature in the range of 351~370 °C , flue gas temperature in the range of 191~210 °C, SO2 volume fraction of (293~602)×10–6, NO volume fraction of (588~893)×10–6, activated carbon injection quantity of 0.5 kg/h, reaction space velocity of 4 000 h–1, and flue gas flow rate of 400~500 m3/h.